AGRICULTURE AND BIOTECHNOLOGY CENTRES OF THE PAEC: A RESUME - Naqvi, Mujtaba (The Nucleus, 2020)
Pakistan recognized the role of nuclear techniques in agricultural and other biological research and started establishing goal-oriented, multi- disciplinary institutions to help agricultural research in the country. A core manpower was trained and centres established in the cities where most of the agricultural research was located; the objective was to supplement the research activity in areas where nuclear techniques would have a clear advantage. The first centre was established at Tandojam, Sindh and others at Faisalabad, Mymensingh, Peshawar and again at Faisalabad. Apart from agricultural research, these centres utilized their facilities and ventured into other areas such as biotechnology and can now take some pride in contributing in the country's economy and in development of human resource and helping develop a science culture in the country. With better management systems, the inputs seem to have been better utilized. That the end users and the government have recognized the contributions of these centres is evident from the number of farmers visiting these institutions for advice and the number of medals awarded to their scientists by the government. These institutes could, perhaps, have done even better yet it seems their positive contributions outweigh their deficiencies. In this piece of writing a brief history of these institutions is given and some information provided about the raison for their programmes and the environment under which the programmes were executed. A few of their salient achievements have also been mentioned.